2007
DOI: 10.1007/s00259-007-0456-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and diagnostic accuracy of [18F]FDG-PET/CT in 190 patients with carcinoma of unknown primary

Abstract: FDG-PET/CT imaging is very helpful in the search for the presence of a malignancy in patients with carcinoma of unknown primary syndrome. FDG-PET/CT is less accurate in identifying exactly the site of a primary. Discovery of a hypermetabolic lesion was associated with the worst survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 25 publications
4
45
1
3
Order By: Relevance
“…To date, only one study, by Fencl et al, suggested that FDG-PET/CT in CUP patients might indeed affect outcome. 31 In this series, the survival rate of CUP patients with at least one hypermetabolic lesion proved significantly lower when compared with the remaining CUP patients. Additional studies addressing this issue are warranted.…”
mentioning
confidence: 59%
“…To date, only one study, by Fencl et al, suggested that FDG-PET/CT in CUP patients might indeed affect outcome. 31 In this series, the survival rate of CUP patients with at least one hypermetabolic lesion proved significantly lower when compared with the remaining CUP patients. Additional studies addressing this issue are warranted.…”
mentioning
confidence: 59%
“…By using a set of defined search and selection criteria we identified eight studies in the PubMed database evaluating 18 F-FDG PET/CT in this patient population. Furthermore, analysis of these studies revealed that relevant data could be extracted from only four of these publications [13][14][15][16]. Of these four studies, only the study by Gutzeit et al [18] used a diagnostic CT scan with a standard radiation dose (130 mAs) and i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Four articles/studies were excluded for the following reasons: (a) duplicate study [13], (b) data on CUP patients with extracervical metastases were not extractable [14,15], and (c) part of the study population underwent 18 F-FDG PET alone and was not analyzed separately from patients undergoing 18 F-FDG PET/CT [16].…”
Section: Literature Search and Study Descriptionmentioning
confidence: 99%
“…Cette technique qui dé tecte des processus hypermé taboliques a l'avantage d'une ré solution spatiale é levé e (aux alentours de 5 mm) et de permettre l'exploration du corps entier en un seul examen. Son utilisation, en cas de mé tastase d'origine indé -terminé e, paraît logique et pourrait thé oriquement guider toute investigation complé mentaire [2,9,11,26]. Toutefois, la sensibilité est variable d'un type tumoral à l'autre, moindre dans les cancers prostatiques, ré naux et hé patocarcinomes et globalement dans les tumeurs faiblement prolifé ratives [12,27].…”
Section: Imagerieunclassified